PELATIHAN CABANG OLAHRAGA FUTSAL UNTUK MENINGKATKAN MINAT DAN BAKAT REMAJA - Muhammad Dhika Almaghribi; Azi Faiz Ridlo; Bujang Bujang (An-Nizam, 2022)
This paper is to report on the results of the Bekasi UNISMA Community Service Program in 2022 about increasing the knowledge, skills, interests and talents of teenagers in playing futsal at Pondok Ungu Permai Blok B RW 08 Kaliabang Tengah Village, Bekasi City. The underlying problem is the lack of increased interest and talent in adolescents who are influenced by the lack of skill education and prefer to play online games than exercise. To overcome this problem, KKN students held futsal training for teenagers directly. The purpose of this activity is to improve technical skills in playing futsal, increase body immunity during the pandemic and reduce excessive online game play. The direct training is held every Sunday starting from 19 February 2022 – 13 March 2022 at 15.00-17.00 WIB in the field of RT 06 RW 08. The implementation of this activity has a positive impact on children and youth, such as increasing knowledge techniques in futsal games, increase interest and skills in playing futsal and reduce the risk of eye damage caused by playing online games for too long. This activity has a good influence on children and adolescents to increase their interests and talents and prevent addiction to playing online games that can damage the health of the eyes and mind.